Obtención de cepas de lactobacillus SPP. del estómago del chame (Dormitator latifrons) como potencial probiótico en alimentación agropecuaria - Macías Martínez, Anthony Gabriel (2023)
In the present research we sought to isolate strains of Lactobacillus spp. from the stomach of the chame (Dormitator Latifrons) as a potential probiotic for agricultural feed, bibliographic and descriptive methods were used to carry out the research, as well as for the process of identification of the type of Lactobacillus spp. a molecular identification test of microorganisms was performed by polymerase chain reaction (PCR) resulting in obtaining Lactiplantibacillus plantarum within the digestive tract of chame (Dormitator Latifrons) giving us as a result a probiotic microorganism suitable for use in the food industry, as well as for agricultural animal feed, due to the great benefits in food conversion and health, preventing gastrointestinal problems.